A preliminary design of lactating chair : an ergonomics approach - Mohd Faiz, Zulkifli (2009)
This project investigates the effect of position applied during breast feeding to the mothers. Most of the mothers prefer to breastfeed their babies while sitting and they tend to have back pain or other pains because of there is no chair in the market specialize in that purpose. Aware of that, this project is being conducted in order to enhance the existence chair in the market to fix the mother’s body posture and to reduce the possibility of Musculoskeletal Disorder (MSD) which is related to pains at certain part of the bodies such as back pain due to wrong body posture while doing works. The design was sketched based on the review on past researches and studies done on designs of ergonomics chair. This project would be applied SolidWork software to design the lactating chair as the design can be 3-D drawn. A survey using questionnaire is also being conducted in order to collect the data related to the design of the chair. The design is then simulated using Finite Element Analysis software. This process will involve the critical parts only where most of the loads applied such as on the headrest, backrest, seat and also the base. From the analysis of the questionnaire, the answers show that most of the mothers agreed with the features included in the design of the lactating chair. The analysis of the design using Finite Element Analysis software shows that the selection of steel ASTM A-36 is the best material for the main frame of the chair as there are only small displacements on the critical parts when acted with forces.